RANCANG BANGUN REACTION TIMER DENGAN KEYPAD DAN PENYIMPAN DATA - Muhammad Ikhwan Ardiansyah (Integrated Lab Journal, 2018)
Reaction time became one of the discussion in the Work Design Analysis and Ergonomics. Reaction time is used to measure work performance of a worker. A person who reacts quickly when subject to stimulation, indicates that the person has a high performance. Thus the high or low performance of a person is measured on the basis of the quick or slow of a person in reacting to the stimulus. This research will discuss about how to design and build a reaction timer built microcontroller with input in the keypad which equipped with data storage device.